Respuesta :
f(x)=-x^2+1
for -a
remember pemdas
exponenets before multiply
for -x^2, it is (x^2) first, then times -1
f(x)=-(-a)^2+1
f(x)=-(a^2)+1
f(x)=-a^2+1
for -a
remember pemdas
exponenets before multiply
for -x^2, it is (x^2) first, then times -1
f(x)=-(-a)^2+1
f(x)=-(a^2)+1
f(x)=-a^2+1
Answer:
[tex]f(-a)=-a^2+1[/tex]
Step-by-step explanation:
We have been a function [tex]f(x)=-(x^2-1)[/tex]. We are asked to simplify our function at the indicated value [tex]f(-a)[/tex].
To find [tex]f(-a)[/tex] for our given function, we will substitute [tex]x=-a[/tex] in our given function as:
[tex]f(-a)=-((-a)^2-1)[/tex]
We know that a negative number raised to an even power results in positive, so our function would be:
[tex]f(-a)=-(a^2-1)[/tex]
Using distributive property [tex]a(b+c)=ab+ac[/tex], we will get:
[tex]f(-a)=-1*a^2-1*-1[/tex]
[tex]f(-a)=-a^2+1[/tex]
Therefore, the value of [tex]f(-a)[/tex] is [tex]-a^2+1[/tex].